Analysis of lateral redistribution of a plasma membrane glycoprotein- monoclonal antibody complex [corrected] [published erratum appears in J Cell Biol 1988 Apr;106(4):following 1403] (The Rockefeller University Press, 1988)
The lateral redistribution of a major murine glycoprotein, GP80, was studied on locomoting fibroblasts, using rhodamine-conjugated mAbs and ultralow light level digitized fluorescence microscopy. Confirming an earlier study (Jacobson, K., D. O'Dell, B. Holifield, T.L. Murphy, and J. T. August. 1984. J. Cell Biol. 99:1613-1623), the distribution of GP80 was coupled with cell locomotion; motile cells exhibited a gradated distribution of the GP80-mAb complex over the cell surface, increasing from the front to the rear, whereas stationary cells exhibited a nearly uniform GP80 distribution. By monitoring locomoting single cells, we found the gradated fluorescence distribution to be maintained as an approximate steady state. Newly extended leading edges were almost devoid of the fluorescence labeling. This was strikingly demonstrated in prechilled cells in which the extension of fluorescence- free leading edges caused a pronounced boundary between fluorescent and nonfluorescent zones. Subsequently this boundary eroded gradually in a manner consistent with diffusional relaxation. Evidence indicated that the GP80 redistribution was primarily caused by the lateral motion of GP80 in the plasma membrane and not via intracellular membrane traffic. Two cell locomotion models which, in principle, could account for the GP80 redistribution were tested: the retrograde lipid flow (RLF) model (Bretscher, M. S., 1984. Science (Wash. DC). 224:681-686) and an alternative hypothesis, the retraction-induced spreading (RIS) model. The predictions of these models were stimulated by computer and compared with experiment to assess which model was more appropriate. Whereas both models predicted steady-state gradients similar to the experimental result, only the RIS model predicted the lack of retrograde movement of the fluorescent boundary.